A PRODUCTION OF BIOGAZ IS ON WASTES OF ALCOHOL INDUSTRY OF UKRAINE (World Science, 2019)
Effective utilization of wastes of an alcohol industry is investigational in bioenergetics with the aim of reduction to energy dependence of enterprises, providing of power autonomy of subjects of menage, increase of economic efficiency, improvement of ecological situation.